Engaging the Bible. Critical Readings from Contemporary Women, Choi Hee An & Katheryn Pfisterer Darr (Eds.) : book review - Klopper, Frances (Old Testament essays, 2009)
The world having become a global village has implications for the interpretation of biblical texts. Feminist and womanist critics from various ethnic and social groupings remind us that there can no longer be claims of dominant feminist readings since all readers, as products of their times and contexts, bring to the text their struggles and experiences. An and Darr's book illustrates this hermeneutical principle in offering five essays by women theologians representing different cultural, ethnic, social and sexual orientation perspectives.